TANGGUNG JAWAB PENYIDIK DAN PENUNTUT UMUM ATAS PUTUSAN BEBAS DAN LEPAS DARI SEGALA TUNTUTAN HUKUM DALAM TINDAK PIDANA KORUPSI - Rian Van Frits Kapitan (IBLAM Law Review)
The purpose of this paper is to find out the responsibilities of investigators and public prosecutors for acquittals and release from all lawsuits in corruption cases. The research method used is normative juridical research which focuses on several approaches, namely the case approach, the conceptual approach and the statute approach. The author's conclusion regarding the responsibility of investigators and public prosecutors for acquittals and acquittals in corruption cases is that there is an indirect responsibility in which the state through the Minister of Finance is obliged to pay compensation for people whose corruption cases are acquitted or released from all lawsuits if there is a claim for compensation.